The Role of Guidance and Counseling in Supporting the Successful Implementation of the Independent Curriculum in Middle Schools - Damanik, Nurmalia; Lubis, Saiful Akhyar; Darmayanti, Nefi (Yayasan Ilomata, 2024)
This study aims to explore the implementation of counseling guidance in the context of the success of the Independent Curriculum in secondary schools. The Independent Curriculum is known as an initiative to promote competency-based education with an emphasis on developing relevant skills, knowledge, and attitudes for students. The research method used is a qualitative study with a phenomenological approach. The research participants consisted of counseling guidance teachers, school principals, and students involved in the implementation of the Independent Curriculum. Data collection was carried out through in-depth interviews and participatory observations. The results of the study show that the implementation of counseling guidance plays an important role in supporting the success of the Independent Curriculum. The findings highlight that counseling guidance assists students in identifying and developing competencies in accordance with the demands of the new curriculum. In addition, the role of counseling guidance teachers in facilitating students' understanding and motivation towards the new curriculum is also very important. This study provides practical implications for the development of further education policies in integrating the role of counseling guidance as the main supporter in the success of the Independent Curriculum. It is hoped that this research can be the foundation for the development of a more effective counseling guidance program in supporting broader educational goals.